Analysis of the Influence of Financial Performance on Tax Effectiveness in Banking Companies Listed on the IDX in the 2020-2023 Period - ISNAINI, Hamidah Nur; PERMANA, Ngadi; AMELIA, Yessica (PT Keberlanjutan Strategis Indonesia, 2025)
This study analyzes the effect of financial performance on tax effectiveness in banking companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2023 period. The sample includes 32 banks (128 bank-year observations) using a panel Random Effects Model (REM) approach. The independent variables include Return on Assets (ROA), Capital Adequacy Ratio (CAR), and Cost Efficiency Ratio (BOPO), while tax effectiveness is proxied by the Effective Tax Rate (ETR). The results show that ROA and BOPO have a significant negative effect on ETR, indicating that higher profitability and better operational efficiency are correlated with lower effective tax rates. Conversely, CAR does not show a significant effect. Simultaneously, all three financial performance indicators significantly influence ETR, the main contribution of this study is the integration of profitability and operational efficiency dimensions to explain variations in ETR in the Indonesian banking sector during the pandemic and post-pandemic phases, periods rife with regulatory changes and risk dynamics. Robustness procedures were employed to ensure the reliability of the findings, including the use of clustered standard errors at the entity level, extreme value winsorization, and alternative estimates (fixed effects), as well as replacing the proxy with cash ETR; all of which yielded directional inferences. ETR is defined as pre-tax income tax expense. Limitations include potential endogeneity and the lack of governance indicators; further research is recommended to incorporate instruments/lags, governance variables, and risk dimensions to enhance causal understanding.